The Cell cycle : a practical approach - Fantes, Peter; Brooks, Robert (IRL Press, 1994)
The Practical Approach Series. Softcover version. The use of recombinant D.N.A. and related technologies has revealed the extraordinary degree to which cell cycle control mechanisms have been conserved through eukaryotic evolution. The availability of genes and gene products derived from different organisms has greatly extended what is experimentally possible. As a result, many researchers are now faced with the need to handle a far wider range of organisms and must therefore be acquainted with the ever-increasing arsenal of experimental techniques. This book is a compilation of key techniques currently used in the most popular experimental systems. The book describes how specific organisms or cell types are handled and focuses on particular techniques that are applicable to any cell type. A wide range of biochemical, genetic, and cellular manipulations are described. Students and researchers in cell and molecular biology will welcome this accessible, useful new guide.
Practical approach series ; 137
Keywords: cytologie, klinická cytologie; buněčný cyklus; Cell Cycle